Desenvolvimento de um sistema de insensibilização elétrico de fluxo continuo (75v/3seg) para o abate de tambatinga (Colossoma macropomum x Piaractus brachypomus), como alternativa a termonarcose em água e gelo - Ribeiro, Thamiris Caetano Silva (2017)
With the need to minimize pre-slaughter stress and slaughter of fish, stunning methods have been used by the fish-processing industries, among them, termonarcosis is a commonly used but contested method of animal welfare. The objective of this study was to compare the 1: 1 thermonarcose (water and ice desensitization) method and the electrosurgery method (electrical discharge desensitization), as this may lead to a rapid transition to unconsciousness. A total of 40 tamboshes (Colossoma macropomum x Piaractus brachypomus) with a mean weight of 1,240 ± 0,19g were submitted to stunning by termonarcosis (T1) and by eletronarcosis (75V / 3seconds) (T2). The analysis of physiological responses (glycemia, chloride and total protein), behavior (swimming motion, loss of balance, opercular movement, leakage reaction, ocular rolling and reflex movement) and meat quality (water retention capacity, pH and color). Fish stunted by eletronarcose presented higher values of muscle pH at hours 1 and 3 postmortem (6.61 ± 0.239b and 6.51 ± 0.134b) and took longer to enter rigor mortis. T1 presented lower scores of the measured reflexes, being swimming movement (0.35 ± 0.33a), loss of balance (0,1 ± 0,45a), opercular movement (0.3 ± 0,47a), reaction to leakage (0.2 ± 0.41a), ocular bearing (1.00 ± 0.86ª) and reflex movement (0.15 ± 0.49a). Both treatments did not present significant differences for water retention capacity for T1 (16.87 ± 2.66) and T2 (16.12 ± 2.89), presenting high values. The values of L * for T1 (63.39 ± 1.36) and T2 (63.95 ± 1.12), and b * for T1 (8.36 ± 1.32) and for T2 (8.06 ± 0) , 60) did not present significant differences, but a * values were significantly higher in T2 (7.91 ± 0.96) than in T1 (7.26 ± 1.06). Regarding blood parameters, there was a significant difference only in glycemia for T1 (121.70 ± 25.58a) and T2 (124.95 ± 33.67b) and protein for T1 (3.46 ± 1.553a) and T2 (3, 57 ± 0.976b). It was concluded that termonarcose presented lower responses to preslaughter stress, presenting better quality in relation to eletronarcosis